শহীদ সন্তোষচন্দ্র ভট্টাচার্য, ১৯১৫-১৯৭১ - চক্রবর্তী, রতন লাল (জীবনী গ্রন্থমালা)
Biography of Santoshacandra Bhaṭṭācārya, 1915-1971, professor of History of the University of Dhaka, Bangladesh, a martyr of 1971 Bangladesh revolution; includes sampling of his writings.